Cheerleading – a tool to achieve wellness culture in the Bulgarian school (Research Announcements "Heritage BG", 2025)
Cheerleading is an interactive tool to motivate young people to a wellness lifestyle. In the subject of physical education and sports they can be practiced as an extracurricular form of education. They contribute to the physical, aesthetic, musical, dance and intellectual development of students. Wellness indicators contribute to a sustainable emotional state with a cheerful, creative spirit, which supports the construction of a positive and stimulating work environment. School Wellness is regulated by the 9th key competence of the student in the Law on Preschool and School Education. References:Dimitrova et al. 2018: Dimitrova Bistra, Mincho Polomenov, Vesela Treneva, Irina Nesheva, Vessela Ivanova, Dimitar Trendafilov. Sotsialna znachimost na uelnes (wellness) kulturata: sravnitelen analiz po danni ot nauchni izsledvania na Galap interneshanal. Monografia. Izd. Avangard, Sofia: 89-104.Dimitrova et al. 2020: Dimitrova Bistra, Pencho Geshev, Vesela Treneva, Vessela Ivanova, Vasil Petrov. Dinamika na indeksite za uelbiyng i shtastie: sravnitelen analiz po svetovna baza danni, saobrazno statisticheski danni ot dokladi na OON. Monografia. Izd. Avangard, Sofia.Dimitrova et al. 2021: Dimitrova, Bistra, Nikolay Izov, Velichka Alexandrova, Rumen Iosifov, Darinka Ignatova, Dimitar Trendafilov, Vasil Petrov, Gergana Vasileva. Smart kognitiven instrumentarium. Vŭnshna otsenka na profesionalni kompetentsii za kadri v Nishov turizém. NSA Pres, Sofia, 58-60.Minkovska 2021: Minkovska, Gergana. Vazpitatelni aspekti na grupovite muzikalno-dvigatelni deinosti pri 6-7 godishni detza. Ph.D Dissertation, SU ‘St..Kliment Ohridski’, 67-69.Nesheva 2010: Petkova-Nesheva, Irina. Baton twirling i majoretki. Sbornik V mejdunaroden nauchen kongres SSA, Olimpijski sport, sport za vsichki. I chast, NSA, Izd. Tip-top press, Sofia, 381-384.Chalakov 2020: Chalakov, Milen. Optimizing the Control of Technical Performance of Forehand Stroke Among 12-years-old Tennis Players Using Martin’s Sigma Method. Trakia Journal of Sciences, No 18 (1), 682-688.Dimitrova 2017: Dimitrova, Bistra. Recreative Industry, Innovations and the Bulgarian Educational Model for Specialised staff. Conference: International Scientific Congress ‘Applied Sports Sciences’. Sofia, 406-410.Donev et al. 2019: Donev Jordan, Stoyan Andonov, Stefka Djobova, Jordan Jordanov Donev, Oleg Hristov, Ivelina Kirilova, Stoyan Bahchevanski, Rumen Iossifov, Velichka Aleksandrova, Bogomil Angelov, Nataliq Stoyanova. Comparative Study of Measuring Physical Activity Among Sport Students. International Scientific Congress ‘Applied Sports Sciences’. 15 – 16 November 2019, Sofia, 369-374.Konchev 2019: Konchev Mihail. Big Data, Neural Network and Predictive Analytics: Application in the Field of Sport. International Scientific Congress ‘Applied Sports Sciences’ and Balkan scientific congress ‘Physical Education, Sports, Health’ in Sofia, Bulgaria, 2019, 393-397.Trendafilov, Dimitrova 2013: Trendafilov, Dimitar, Bistra Dimitrova. Aqua Spinning as Antistress Health Prevention. Sport Mont, No XI (37-38-39), 467-473.
Keywords: Cheerleading; Baton twirling; recreational physical activity; healthy programs; Wellness at school